Qowaidul khomsah dalam menentukan regulasi crypto: implementasi qowaidul khomsah dalam menentukan regulasi crypto - putri, sofiyah amalun (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has encouraged innovation in the financial sector, one of which is cryptocurrency. The existence of this digital asset has sparked debate in Islamic legal studies, particularly regarding its halal status both as a medium of exchange and as an investment instrument. This study aims to analyze the concept of cryptocurrency from an Islamic perspective and to examine the application of Al-Qawaid al-Khamsah as a foundational framework in determining regulations and justifying the fatwas issued by the Indonesian Council of Ulama (DSN-MUI) regarding cryptocurrency. The method used in this research is a literature study with a normative approach, conducted through an analysis of relevant fiqh principles and fatwas. The results indicate that Al-Qawaid al-Khamsah plays an important role in evaluating aspects of benefit, potential risk, elements of uncertainty, the purpose of use, and public practices related to cryptocurrency. Based on these considerations, the DSN-MUI has determined that cryptocurrency is not permissible as a medium of exchange, but it may be used as a commodity under certain conditions, as it is considered to contain elements of gharar, maisir, and dharar. Therefore, fiqh principles serve as an important foundation in formulating sharia regulations that are responsive to developments in the financial sector.